Computational and experimental modeling of curved crack effects on the dynamic response of plate structures - Alshammari, Yousef Lafi A.; Khan, Muhammad A.; Doğanay Kati, Hilal (Tech Science Press, 2026)
Cracks can severely degrade the integrity and service performance of plate structures. Although most existing studies focus on identifying straight crack patterns using dynamic response data, curved crack paths have received far less attention, despite being more realistic in practice and having a stronger influence on structural behaviour. This study presents a computational and experimental framework for analyzing and identifying curved crack paths in cantilever plate structures based on dynamic response characteristics. Curved crack paths are modelled using second-order polynomial equations. Finite Element Analysis (FEA) is employed to evaluate the effects of polynomial coefficients and crack end abscissa (x-end) on natural frequency and resonance amplitude, while experimental modal analysis (EMA) on damping ratio. Forward and inverse identification models are then developed using linear regression (LR) and artificial neural networks (ANN) to predict dynamic response characteristics and estimate crack path. Results show that the quadratic coefficient (a) and linear coefficient (b) of the crack path have the most decisive influence on the plate’s vibration characteristics, whereas the constant term (c) has a negligible effect. Also, the crack paths with greater curvature and inclination, represented by higher a and b coefficients, especially at smaller end abscissae (x-end), tend to reduce natural frequencies and increase vibration amplitudes and damping ratios. In contrast, smoother, less curved cracks exhibit the opposite behaviour. These curved crack geometries cause greater stiffness degradation by altering both axial and shear stiffness. Consequently, local flexibility and energy dissipation increase due to enhanced crack-surface interaction and localised deformation. The proposed computational models are experimentally validated using 15 fabricated plates with different curved crack profiles, demonstrating high prediction accuracy. Overall, the study enhances the computational identification and characterization of curved cracks in plate structures, contributing to improved damage assessment and structural health monitoring (SHM) based on dynamic response.
Keywords: 49 Mathematical Sciences; Applied Mathematics; 4901 Applied mathematics; 4903 Numerical and computational mathematics; Curved crack paths; computational modeling; dynamic response analysis; finite element analysis (FEA); artificial neural networks